INTERNATIONAL POLITICO-LEGAL MECHANISMS OF RELIGIOUS TOLERANCE - Toshpulotov Shokhijakhon Eshpulotovich (International Journal of Business, Law and Political Science, 2024)
Religious tolerance is a fundamental principle underpinning international human rights and diplomatic relations, promoting peace and coexistence in diverse societies. Various international politico-legal mechanisms have been developed to foster religious tolerance, yet the effectiveness and integration of these mechanisms in different geopolitical contexts remain inadequately explored. There is a need for a comprehensive evaluation of how international frameworks and legal instruments address and enforce religious tolerance, particularly in regions with entrenched sectarian conflicts. This study aims to analyze the international politico-legal mechanisms designed to promote religious tolerance, assessing their implementation, effectiveness, and impact on global and local levels. The research finds that while international treaties and agreements provide a solid foundation for promoting religious tolerance, discrepancies in enforcement and varying degrees of commitment among nations limit their overall effectiveness. This study contributes by offering an integrated assessment of both the theoretical and practical aspects of international mechanisms for religious tolerance, incorporating case studies to illustrate diverse applications and outcomes. The findings suggest the need for more robust and universally accepted frameworks, as well as improved mechanisms for enforcement and accountability, to enhance the global promotion of religious tolerance and address sectarian tensions more effectively.